The Status of Pig Welfare in Selected Districts of Uganda: Implications for Health and Productivity Interventions - Dione, Michel M.; Oba, Peter; Nsadha, Zachary; Asmare, Kassahun; Knight-Jones, Theodore J. D.; Doyle, Rebecca E. (Frontiers in Animal Science, 2022)
We conducted a pig welfare survey in four high pig producing districts in central Uganda, namely Masaka, Mukono, Mpigi and Wakiso in 2021. Data were collected from 270 pig farms, and a total of 3561 pigs, and consisted of resource-based (housing and water supply), animal-based (pig body condition and physical injuries) and management-based (records of morbidity and mortality) indicators of pig health and welfare. Data on animal and resource-based indicators were obtained from physical assessments of pigs and farm facilities, while management indicators and demographic details were collected by farmer interview. Across all farms, sow mortality in the last 12 months was reported to be 2.5% (95% Confidence Interval: 1.7, 4.8%). Animal-based indicators identified 9% (6.1, 13.7%) of sows with scouring/diarrhea, 7.6% (4.7, 11.5%) with lameness and 92% (85.1, 96.7%) of (dry or lactating) sows were found to be ‘skinny’ with a body condition score of 1 or 2. In addition, piglet mortality was as high as 10.2% (8.5, 12.9%). A total of 19% of sows were partially or completely restricted from free movement inside pens. Ninety-three per cent of sows had continuous access to water, but only 48.8% of the water supplies were clean. Twenty per cent of farms reported sows experiencing stillbirths , 15% reported ill thrift, 12.5% reported respiratory disease and 10.8% reported gastrointestinal disease. Wakiso district registered the lowest pig mortality which was significantly lower compared to the other three districts. This study reveals Ugandan pigs are exposed to undernutrition (high proportion of pigs with poor body condition score), dirty water, high mortality, physical injuries, poor housing, and health challenges (stillbirth, ill thrift and GI disorders). Meaningful change to farmer livelihoods and pig welfare can be made by designing simple interventions that target improve housing structures, provision of cooling facilities especially during hot periods (heat stress) and bedding materials. The findings also represent a benchmark for the assessment of the effect of such interventions designed to improve farm health and productivity.